Mecanisms of the chemical crosslinking to obtain the hydrogels: Synthesis, conditions of crosslinking and biopharmaceutical applications (Research, Society and Development, 2023)
Hydrogels are three-dimensional polymer matrices with recognized biomedical applications. Chemically crosslinked hydrogels offer greater mechanical stability than physically crosslinked hydrogels due to the covalent bonds between their polymeric chains. The preparation of hydrogels by chemical crosslinking involves three basic components: monomer, initiator and crosslinking agent, which must be present in proportions that do not alter the integrity of the hydrogel. The chemical crosslinking mechanism can be designed from reactions between complementary functional groups, ultraviolet light reactions, radical polymerization, high energy irradiation, among others. In this review, we revisit the chemical crosslinking mechanisms involving synthetic or natural polymers. Finally, biomedical applications of hydrogels are discussed, such as drug delivery, cell culture, tissue engineering, cancer therapy, among others.